(untitled) (Al-Academy, 2020)
The current research studies the digital techniques in order to identify the treatments with graphic techniques for the theatrical scene, which includes a number of programs and treatment tools with digital technique to identify the visual and aesthetic dimensions and outputs achieved in the design of the theatrical scene in addition to the options, that they provide in the design of a system of hypotheses for the theatrical world, In order to be an experimental mediator in achieving the creative hypothesis, which limited the research with a pivotal objective which is: identifying the digital techniques employed in the graphic digital design for the scene in the theatrical show. The research lies in its objective limits stated in the methodological framework i.e. Treatments with graphic techniques for the scene in the theatrical show, and employing it procedurally as a technical treatment in the design and construction of the theatrical scene. The research consists of the methodological framework in which the researcher determined the research problem, importance, the need for it, and its aim, in addition to specifying its terms procedurally. The theoretical framework consists of two sections: the first: the graphic techniques (digital design programs). The second section: employing the computer and its graphic techniques in the design of the theatrical scene. This section ended with the indicators from the theoretical framework. The researcher, in the research procedures, addressed the research sample. The researchers come up with the following conclusions including: 1- The treatments with the graphic techniques for the theatrical scene provide an infinite capacity of creative options for the scenographic designer with the multiplicity of the hue degree, glossiness and purity, and the ability for constructing the figure in the scenographic composition in addition to the flexibility in the design, amendment and implementation. 2- The treatments with the graphic techniques for the theatrical scene provide huge amount of structure multimedia capabilities for the explanatory figures for the themes in the dynamism of the dramatic events. 3- The treatments with the graphic techniques for the theatrical scene achieve a profit through reducing the materialistic cost, compared to the traditional scene, let alone the weight, size, life span in addition to the time.